The effectiveness of corporal punishment in dealing with deviant behaviour in pupils in schools - Wadesango, N.; Gudyanga, Ephias; Mbengo, F. (MCSER Publishing, 2016)
The research set out to investigate and establish the effectiveness of corporal punishment in dealing with deviant behaviour in pupils in Chibuwe Cluster Schools in Chipinge District. The research was prompted by the recurrence of deviance in pupils even after numerous attempts to control and eradicate it with corporal punishment. Descriptive survey research design was used. Stratified random sampling was done to create a sample representative of the population. The sample comprised twentyfive pupils, fifteen form four pupils and ten grade seven pupils. There were also twenty-five teachers, fifteen secondary school teachers, ten primary school teachers as well as five school heads and five members of the school development committees which summed up to sixty respondents. Respondents were sampled from two rural primary and three rural secondary schools selected from eleven schools in the cluster. Data were collected through self administered questionnaires and face to face interviews. The study found out that there is very rare to no procedural and recommended corporal punishment in Chibuwe Cluster Schools. It was recommended that schools should widen and diversify their disciplinary strategies to include rewards, discussions, explanation and others.